WORD FORMATION (WORTBILDUNG) IN THE GERMAN LANGUAGE AND ITS IMPORTANCE IN THE EDUCATIONAL PROCESS - Begimqulova Xolniso Saidmurod qizi (Bright Mind Publishing, 2026)
Word formation (Wortbildung) is one of the most productive and essential linguistic processes in the German language, playing a significant role in vocabulary expansion, semantic development, and communication efficiency. German is known for its rich system of compounding, derivation, conversion, abbreviation, and borrowing, which enables speakers to create new lexical units according to communicative needs. In the educational process, understanding German word formation is crucial for learners because it improves vocabulary acquisition, reading comprehension, writing competence, and translation skills. This article explores the main types of word formation in German, analyzes relevant scientific literature, and discusses pedagogical methods for teaching Wortbildung effectively.
Keywords: German language, Wortbildung, word formation, derivation, compounding, conversion, vocabulary teaching, language education, morphology, linguistic competence.